INTRODUCING NEW RELIGIOUS IDEAS TO MATHLA’ULANWAR: KH. UWES ABU BAKAR (1939-1973) - Iman Wahyuddin (Pascasarjana IAIN Sorong, 2018)
Mathla’ul Anwar was established in 1916 by several Bantense kiyais, an Indonesian term used to attribute religious teachers, including KH. Tubagus Muhammad Sholeh, KH. Entol Muhammad Yasin, KH. Mas Abdurrahman, KH. Abdul Mu’thi and others Mathla’ul Anwar is one of the largest Muslim associations in Indonesia along with Nahdlatul Ulama or NU (mostly seen as the most prominent representative of the “traditionalist” Muslim groups established by several pesantren leading religious teachers in 1926 and Muhammadiyah (the largest group of the modernist or reformist Muslims established in 1912). KH. Uwes Abu Bakar wrote several treatises and books, including Al-Waqud, Targhibul Atfal, Surat Imam Malik kepada Harus AlRasyid dan Wazirnya, Tuntunan Bergaul and Bermasyarakat, and Ishlahul Ummmah Fi Bayani Ahli Sunnah Waljamaah. KH. Uwes divided Islamic law into two parts, (ibadah) divinely based ritual that was immune from changes and muamalah that was a result of human interpretation and was vulnerable to changes. He viewed that all products of ijtihad of ulama should be included into the latter part. The diversity of those products of thought was natural as every human had his own method of interpretation as well as his conclusion. At the same time, as a mankind, those ulama were also not immune from making errors. Critical attitudes were highly required in order to adhere or reject certain religious opinions of ulama. Since the focus of the study is Mathla’ul Anwar, I would like to focus on the impacts of this religious renewal towards members ofMathla’ul Anwar. To view the impacts of this religious renewal, it is important to highlight the succeeding developments of religious thought within Mathla’ul Anwar after the publication of the book. There were at least three general features of religious thought growing in Mathla’ul Anwar in 1970s